In Vitro Doubled Haploid Production of Bacterial Blight Resistant Plants from BC2F1 Plants (Ranbir Basmati X Pau148) Through Anther Culture - Mridhu Sharma; Mamta Sharma; A.K. Singh; R. K. Salgotra; Manmohan Sharma; Bupesh K. Sharma; S.K. Gupta (Hasanuddin University, 2022)
Doubled haploid plants are very important for the development of complete homozygous plants from heterozygous parents in one generation as they possess duplicate copy of haploid chromosome. Haploid production is easily obtained from in vitro anther culture. The present study was undertaken with the objective to develop doubled haploids using anthers for in vitro induction of callus on N6 medium supplemented with various combinations and concentrations of 2,4-dichlorophenoxy acetic acid (2,4-D) (0.5-2.5 mg/L), Kinetin (0.5-1.0 mg/L) and Naphthalene acetic acid (NAA) (2.0 mg/L) as callus induction medium (CIM). The highest callus induction frequency was obtained when N6 medium fortified with 2,4-D (2.5 mg/L), Kinetin (0.5 mg/L) and NAA (2 mg/L) of 10.07 per cent. The induced callus was sub cultured for shoot regeneration on Murashige and Skoog medium (MS) supplemented with growth regulators: Kinetin and NAA (0.5 mg/L each) in combination with BAP (0.0 - 2.5 mg/L). MS medium supplemented with NAA (0.5 mg/L), Kinetin (0.5 mg/L) and BAP (1.5 mg/L) was most responsive exhibiting regeneration frequency of 28.1 per cent which resulted in maximum regeneration of green plantlets and only 5.21 per cent of albinos. Individual plantlets were separated and immersed in liquid MS medium augmented with NAA (0.5-1.0 mg/L) and BAP (0.5-1.0 mg/L). Maximum rooting was observed in MS medium with NAA (0.5 mg/L) and BAP (1.0 mg/L). The survival rate of in-vitro raised plants was 51.51 per cent. Of these surviving plants, 21 plants were observed to have the sterility percentage above 50 percent and hence can be considered as the doubled haploid plants. Plant DH8 is susceptible and DH20 is heterozygous for gene Xa21. Two plants are susceptible for gene xa13